2015
DOI: 10.1038/nature14431
|View full text |Cite
|
Sign up to set email alerts
|

Neurotransmitter and psychostimulant recognition by the dopamine transporter

Abstract: Na+/Cl−-coupled biogenic amine transporters are the primary targets of therapeutic and abused drugs, ranging from antidepressants to the psychostimulants cocaine and amphetamines, and to their cognate substrates. Here we determine x-ray crystal structures of the Drosophila melanogaster dopamine transporter (dDAT) bound to its substrate dopamine (DA), a substrate analogue 3,4-dichlorophenethylamine, the psychostimulants D-amphetamine, methamphetamine, or to cocaine and cocaine analogues. All ligands bind to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

35
548
1
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 396 publications
(587 citation statements)
references
References 54 publications
(89 reference statements)
35
548
1
3
Order By: Relevance
“…These observations are similar to those reported from the recent dDAT crystal structures (Wang et al, 2015). In fact all reported poses of these docked compounds preserve ~3Å-4Å separation between Y156 and D79.…”
Section: Accepted M Manuscriptsupporting
confidence: 81%
See 4 more Smart Citations
“…These observations are similar to those reported from the recent dDAT crystal structures (Wang et al, 2015). In fact all reported poses of these docked compounds preserve ~3Å-4Å separation between Y156 and D79.…”
Section: Accepted M Manuscriptsupporting
confidence: 81%
“…We augment our ligand binding and functional data with structural results from computational molecular modelling, docking studies and atomistic molecular dynamics simulations, which have been previously shown to be robust methods for predicting the binding sites of various psychostimulants at human DAT (hDAT) in relation to the substrate binding site (Beuming et al, 2008;Bisgaard et al, 2011). We present here, on the basis of the crystal structure from Drosophila melanogaster dopamine transporter (dDAT) (PDB ID: 4XP1) (Wang et al, 2015), a molecular model of 5-MAPB bound to rat DAT (rDAT), in comparison with that of dopamine, amphetamine, 5-APB, MDMA, cocaine and RTI-121 also bound to rDAT. Our studies compare the structural changes produced by various ligands binding to rDAT to the already ongoing work in hDAT models (Hamilton et al, 2013;Hansen et al, 2014;Khelashvili et al, 2015aKhelashvili et al, , 2015b since it is the primary animal model used in functional studies and pre-clinical drug abuse testing.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations